The Thia‐Michael Reactivity of Zerumbone and Related Cross‐Conjugated Dienones: Disentangling Stoichiometry, Regiochemistry, and Addition Mode with an NMR‐Spectroscopy‐Based Cysteamine Assay1. Issue 17 (6th May 2015) - Appendino, Giovanni; Minassi, Alberto; Collado, Juan A.; Pollastro, Federica; Chianese, Giuseppina; Taglialatela‐Scafati, Orazio; Ayyari, Mehdi; Garcia, Victor; Muñoz, Eduardo
Abstract: The cross‐conjugated and electrophilic dienone system of the humulane sesquiterpene zerumbone (1a ) was modified by E / Z photochemical isomerization and/or by removal of homoconjugation with the isolated endocyclic double bond of the medium‐sized ring. The site (C‐6/C‐9), mode (transient or irreversible), stoichiometry (single or twofold), and comparative rates of thiol addition were evaluated using an NMR‐spectroscopy‐based cysteamine assay. Dramatic effects were seen, and this highlights the subtleties of the reaction and the limitations of our predictive power in this field. For biological endpoints sensitive to thiol trapping, a substantial separation between Michael reactivity and biological activity was found for1a and its analogues. This supports the view that shape complementarity plays a critical role in the covalent binding of Michael acceptors to their macromolecular target(s). Abstract : Using the NMR‐spectroscopy‐based cysteamine assay, the thia‐Michael reactivity of the cross‐conjugated dienone zerumbone and its photoisomers and epoxides was investigated, and marked differences were found. For biological endpoints sensitive to Michael acceptors, a substantial separation between reactivity and biological activity was observed.